Isotopic biogeochemical indicators of evapotranspiration and nitrogen flows in a check‐dam catchment in the Loess Plateau, China. (2nd August 2018) - Chen, Shibo; Huang, Yong; Wang, Linhua; Chen, Weiliang; Wang, Yafeng; Gao, Yang
Abstract: The increasingly fragile environment and associative nitrogen (N) biogeochemical cycle have become critical environmental and ecological issues in China's Loess Plateau. However, N flow and N source for typical catchments remain poorly understood in the Loess Plateau. In this study, we measured concentrations and isotopic signatures of N, hydrogen (H), and oxygen (O) in both rainfall and river water. Results showed that baseflow variation in total nitrogen (TN) concentrations ranged from 0.16 to 32.70 mg L −1 . The monthly TN deposition flux and monthly TN wet deposition concentration to river water were shown significant variations between rainy and dry seasons. The range of variation in δ 2 H values for rainfall and baseflow was from −90.0‰ to 19.8‰ and from −67.2‰ to −38.4‰, respectively, whereas δ 18 O–H2 O values ranged from −12.1‰ to +2.7‰ and from −9.3‰ to −3.6‰, respectively. The Local Meteoric Water Line in the check‐dam catchment was δ 2 H = 7.35 δ 18 O + 2.29 ( R 2  = 0.93). Furthermore, NO3 − δ 15 N and δ 18 O values in baseflow ranged from −2.0‰ to +20.5‰ and from +8.0‰ to +15.6‰, respectively. The results indicated that rainfall was affected by below‐cloud secondary evaporation and caused strong isotopic kinetic fractionation to occur during the precipitation process. The NO3 − in runoff was mainly derived from the nitrification of soil organic matter and manure or sewage, for which the proportion of manure or sewage was from 50.5% to 83%.